Wind power derivatives: definitions and applications in the Brazilian market - Bodra, Roberto Andreotti (2022)
This thesis consists of three studies related to the volume risk faced by wind power producers in Brazil. Being an intermittent source, it is still difficult to predict when and how much power will be generated from the wind, posing challenges for producers when estimating their businesses revenues. With still limited choices to offset this type of risk, the objective of this work is to propose financial contracts dependent on wind speed that could serve as hedging instruments for renewable power producers. We performed simulations considering the entire country and five different states over three years for one-month ahead cycles. The first study compares four different wind speed forecast models, and the results show that, although the simple moving average and autoregressive models perform better in a broader sense, when analysing different regions in detail, there is no single model that fits all. The second study uses these wind speed forecasts as inputs to a generation function to estimate wind power utilization indices. The results reveal that, using the autoregressive input, we can obtain good estimates when compared to the numbers published by the ONS. The third study proposes wind power derivative contracts with utilization indices as the underlying asset. Through simulations of wind farm generation revenues, our results show that by using these derivatives combined with price derivatives, producers can reduce their potential losses and unexpected income due to the intermittent nature of the business.